THE EMERGENCE AND EXPANSION OF DEPARTMENT STORES: FROM THE PEAK OF THE XIX AND XX CENTURIES TO ITS REESTRUCTURING IN THE CONTEMPORARY PERIOD - Santos, Flaviane Ramos dos [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2020)
Department stores have emerged in the 19th century as important areas of consumption, which have contributed both to the dissemination of fashion as for consumer democratization just as they were responsible for bringing about major changes in trade patterns. Taking these aspects into account, the aim of this article is to give a historical retrospective of the emergence and expansion of department stores in the world and in Brazil to show how such expansion and development have occurred, as well as in Brazil, coping strategies, adjustment and restructuring nowadays against strong competition with new consumer spaces, primarily, the shopping malls. Besides, we stress some grounds for the significant differences among these commercial spaces in Brazil and their European and US counterparts, most prominently in historical, cultural and temporal factors. To this end, we have used the bibliographic review, above all foreign, in particular to Whitaker (2011), Toboso (2000) and Cuartas (1995) as methodology. To ensure market survival in a competitive marketplace, department stores have somehow, remolded themselves via product diversification and the quest for customer satisfaction and, hence, the adoption of binding strategies.
Keywords: Spectacular consumption; department stores; commerce